State of Emergency in the Republika Srpska: Implementation Consequences - Hadži Stević, Brano (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Due to the extraordinary circumstances caused by the covid-19 virus, numerous states adopted different measures in order to mitigate the consequences of the epidemic, and many of them represented a restriction of human rights and freedoms. This paper is devoted to the analysis of (legal) consequences caused by epidemic measures in the Republika Srpska adopted during the state of emergency. In particular, the legal and sub-legal provisions regulating the actions of authorities in extraordinary circumstances are analyzed, as well as the practice of the Constitutional Court of the Republika Srpska. The aim of the paper is to show that the by-laws, enacted during the state of emergency, were largely in conflict with constitutional and statutory provisions, and it is particularly striking that numerous measures were enacted by non-competent authorities. Although it is an unquestionable obligation of the state to react in a state of emergency, that reaction must be in accordance with the principles of constitutionality and legality, since extraordinary circumstances cannot be an excuse for violating the fundamental values of the legal order. From that point of view, the decisions of the authorities of the Republika Srpska during the state of emergency caused by the covid-19 virus are paradigmatic, but as an anti-model.
Keywords: covid-19, human rights and freedoms, restriction of rights and freedoms, state of emergency, the principle of constitutionality and legality.